Komunikasi Wartawan dalam Reportase konflik Agama - Enjang Muhaemin; Dono Darsono (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2021)
This study aims to explore the meaning and motives of journalists in reporting on religious conflicts and explore journalists' views on the root causes and solutions of religious disputes. This study uses a qualitative approach; the considerations are expected to produce descriptive data, both written, oral, and the behavior of journalists in reporting. The results show that journalists generally interpret religious conflicts as enjoyable, meaningful, and sensitive events. The motives of journalists to report on religious conflicts are more in the interest of documenting newsworthy events, placing problems in a balanced way, and straightening out information confusion in the community. The causes of conflict occur due to differences in perspectives, misunderstandings, intolerance, excessive fanaticism, weak legal umbrella, government indecision, immature religious understanding, the inability of religious leaders to suppress mass emotions, and the presence of certain interested parties. The conflict solution that must be carried out is the existence of a clear and firm legal settlement umbrella and the importance of dialogue in policy formulation..